CartoEvaluation method for assessment of GIS software - Dobesova, Zdena (Geodesy and Cartography, 2013)
The article offers proposals for a new approach to evaluating GIS programs in cartographic functions. The newly proposed CartoEvaluation method is a comprehensive guide in monitoring all cartographic features and in subsequent selection of the program. The CartoEvaluation method is based on Gold-Question-Metric method. CartoEvaluation method was applied for assessment of some desktop GIS software. The result of assessment brings the rank of software. Method can help a user in the choice of GIS program when a user requires a higher cartographic functionality.